The effect of Polyvinylpyrrolidone-Sodium hyaluronate gel on palatal wound healing: a randomized controlled clinical trial - Tugba Bulut; Nuray Ercan (BMC Oral Health)
Abstract Background This study evaluates the effect of polyvinylpyrrolidone sodium hyaluronate gel (Gelclair®) on palatal wound healing, pain, and bleeding following free gingival graft surgery (FGG). Methods Thirty-two patients undergoing FGG were randomly assigned to two groups: the test group received Gelclair® and chlorhexidine mouthwash, while the control group received only chlorhexidine. Patients were called at first, third, seventh, fourteenth and twenty-eighth postoperative days and, Visual Analog Scale (VAS), Wound Healing Index (WHI), hydrogen peroxide (H₂O₂) bubbling scores and bleeding situations were recorded. The Friedman test was used for repeated measures, with the Wilcoxon signed-rank test as post-hoc, and the Mann-Whitney U test for between-group comparisons. Results H₂O₂ test values significantly decreased and WHI values significantly increased over time in both groups (p < 0.050). Test and control groups comparison at time points showed the test group showed significantly lower H₂O₂ test values on days 7, 14, and 28 (p < 0.050) and higher WHI values on days 3, 7, 14, and 28 compared to control group. VAS pain, chewing, and burning scores were also significantly lower in the test group on days 1, 3, 7, and 14 compared to control. While on day 1, the control group had a bleeding rate of 105 times higher than the test group (p < 0.001), no significant differences were observed on days 3 and 7. Conclusions The findings suggest that Gelclair® promotes wound healing and reduces discomfort and bleeding in the palatal donor area after FGG. Trial registration number NCT06610331; Retrospectively registered on 23/09/2024.